A Survey on the Relationship between Responsibility and Job Satisfaction of Nurses working in Teaching Hospitals Affiliated with Tabriz University of Medical Sciences - J Beikzad; A Hoseinpour; M Hejazi Bavil (Tehran University of Medical Sciences, 2014)
Background: Responsibility and job satisfaction are important issues. This study is aimed to investigate the relationship between responsibility and job satisfaction of nurses working in teaching hospitals of Tabriz University of Medical Sciences. Materials ;Methods: Statistical population includes, nurses in teaching hospitals of Tabriz University of Medical Sciences. 316 samples had been selected by stratified random sampling. The data had been collected through a questionnaire and analyzed by using SPSS software. Results: There is a significant relationship between responsibility and two dimensions of job satisfaction (job satisfaction and promotion satisfaction) but there is not significant relationship between responsibility and other three job satisfaction dimensions (satisfaction of supervision and monitoring, satisfaction of colleagues, satisfaction of salaries and payments). Conclusion: Responsibility is an accurate predictor of performance in wide range of occupations .It has a significant relationship with job satisfaction. The more a nurse feels responsible for her or his duties, the more efficient she or he is in delivering health services to patients .Therefor nurses feel more satisfied of their jobs.